-(-9y+3)-5=-5-y

Simple and best practice solution for -(-9y+3)-5=-5-y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(-9y+3)-5=-5-y equation:


Simplifying
-1(-9y + 3) + -5 = -5 + -1y

Reorder the terms:
-1(3 + -9y) + -5 = -5 + -1y
(3 * -1 + -9y * -1) + -5 = -5 + -1y
(-3 + 9y) + -5 = -5 + -1y

Reorder the terms:
-3 + -5 + 9y = -5 + -1y

Combine like terms: -3 + -5 = -8
-8 + 9y = -5 + -1y

Solving
-8 + 9y = -5 + -1y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add 'y' to each side of the equation.
-8 + 9y + y = -5 + -1y + y

Combine like terms: 9y + y = 10y
-8 + 10y = -5 + -1y + y

Combine like terms: -1y + y = 0
-8 + 10y = -5 + 0
-8 + 10y = -5

Add '8' to each side of the equation.
-8 + 8 + 10y = -5 + 8

Combine like terms: -8 + 8 = 0
0 + 10y = -5 + 8
10y = -5 + 8

Combine like terms: -5 + 8 = 3
10y = 3

Divide each side by '10'.
y = 0.3

Simplifying
y = 0.3

See similar equations:

| 41-6x=23 | | f(x)=4x-10 | | 2(0)=-2(0) | | x^2=27i | | 5x+6=66 | | 6y+20=-5+4y | | 2(x)=-2x | | 0.5x=2000 | | 66x-4x^2-272=0 | | 5x+6x+7x=180 | | f(x)=-7x+5 | | f(x)=-2x | | 5x+1=123 | | 4x^5-324x=0 | | f(x)=5x^2-12 | | 5a^3(25b-a)/a-25b | | 6w=7w-5 | | 4x+6=2x+6 | | 25b-a/a-25b | | 4x^2+58x-272=0 | | 1z=50 | | 3y=50 | | -4(11-9x)-8=-4(1-5x) | | 6x-(3x-1)=17 | | 2(-x-1)+1=-3(3x-2) | | -5*(5+7)+215/5= | | 5x+-3y=9 | | 4x-2-5x=10 | | 5(x-6)=3(x+1)-1 | | .25(d-1)=1.5(4d+3)+1 | | 7x+3=8x+10 | | 5+3x=-1 |

Equations solver categories